Does attending an emergency department whilst deployed in Iraq or Afghanistan impact on the mental health of UK Army personnel?. (19th October 2011) - Forbes, Harriet J; Jones, Norman; Woodhead, Charlotte; Greenberg, Neil; Harrison, Kate; White, Sandra; Wessely, Simon; Fear, Nicola T
Abstract : Objectives: Attendances at emergency departments in deployed field hospitals by UK military personnel are frequent. Whilst combat-related injuries are known to impact on post-deployment mental health, less is known about the role other injuries or illnesses sustained on deployment have on subsequent mental health. The impact of attending emergency departments for an injury or illness in Iraq or Afghanistan on post-deployment mental health is examined. Methods: Routinely collected data of emergency department attendances in Iraq and Afghanistan linked with cross-sectional survey-data containing outcomes: probable post-traumatic stress disorder (PTSD), common mental disorders and alcohol misuse. Results: Data from 3896 UK Army personnel were included. 13.8% attended the emergency department. 2.3% were air-evacuated from Iraq or Afghanistan for further treatment. Compared to individuals without an attendance, those air-evacuated for an injury were at increased risk of post-deployment probable PTSD (OR 5.00, 95% CI 2.24 to 11.2). Those air-evacuated for an illness were at increased risk of probable PTSD (OR 4.43 95% CI 1.61 to 12.16) and common mental disorders (OR 2.82, 95% CI 1.43 to 5.56). There was no association between attending an emergency department and alcohol misuse. There was increased risk of probable PTSD among those with a hostile, compared to a non-hostile, injury (OR 3.88 95% CI 1.15-13.06). Conclusions: Being air-evacuated from Iraq or Afghanistan increases the risk of post-deployment mental health problems, particularly probable PTSD. The mental health of individuals air-evacuated from theatre should be monitored. Attending an emergency department whilst deployed had no effect on post-deployment reporting of alcohol misuse.